My body your body - Manning, Mick (London : Franklin Watts, 1996)
My body your body takes a surprising look at bodies-human bodies and animal bodies. We discover, for instance, that although our noses can smell thousands of smells, an elephant can use its nose as an extra arm! But we soon realize that all bodies are different and, what's more they are specially made just for us.
Keywords: Body parts-Fiction